2016
DOI: 10.1039/c6ta02045c
|View full text |Cite
|
Sign up to set email alerts
|

Perylenediimides as non-fullerene acceptors in bulk-heterojunction solar cells (BHJSCs)

Abstract: Perylenediimides are ideal candidates for the substitution of fullerene derivatives as electron acceptors in bulk heterojunction organic solar cells due to their extremely intense light absorbance, high electron mobility and excellent photochemical stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(104 citation statements)
references
References 43 publications
0
104
0
Order By: Relevance
“…To date, numerous small molecule non-fullerene acceptors have been designed and found to provide PCEs that are comparable to those achieved using fullerene derivatives 4,68 . One class of non-fullerene electron accepting materials is low-cost PDI derivatives 7,913 . The BHJ photoactive layer made with PDIs offers a high absorption coefficient in the visible region, good photochemical stability, and good thin film forming properties 7,9,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous small molecule non-fullerene acceptors have been designed and found to provide PCEs that are comparable to those achieved using fullerene derivatives 4,68 . One class of non-fullerene electron accepting materials is low-cost PDI derivatives 7,913 . The BHJ photoactive layer made with PDIs offers a high absorption coefficient in the visible region, good photochemical stability, and good thin film forming properties 7,9,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…The other photoprecursor N602DK was obtained in three steps from 7; dehydration condensation with tosylhydrazide to form hydrazone 9, addition of 9 to C 60 under basic conditions to generate adduct 10, and the deprotection of α-diketone moiety. Note that the reaction between 9 and C 60 afforded a mixture of [6,6]-close and [5,6]-open adducts, which was converted to pure [6,6]-close adduct by a thermal rearrangement at 150…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a large part of the OPV research reported so far, from the study of elementary processes and limiting factors to the optimization of material design and thin-film morphology, has been based on the use of PC 61 BM or PC 71 BM as n-type material. 3 As such, although several high-performance nonfullerene n-type materials have been reported recently, [4][5][6][7][8] fullerenes are still attractive scaffolds in constructing new n-type molecules for OPVs, [9][10][11] if one considers their favorable characteristics and the rich accumulated knowledge.…”
mentioning
confidence: 99%
“…These compounds have been extensively employed as the photo-functional materials for the construction of efficient and tunable electron donoracceptor systems 13,14,15,16,17 and light-harvesting arrays. 18,19,20,21 These dyes have also been used in other photo-physical processes of current interest, such as photocatalysis, 22,23 singlet exciton fission, 24,25 triplet-triplet annihilation, 26 organic photovoltaics, 27,28,29 lasing, 30 fluorescence probing, 31,32,33 and bio-labelling. 34 As compared to other organic dyes, perylene dyes provide a wealth of opportunities for the tuning of their properties via structural modification.…”
Section: Introductionmentioning
confidence: 99%